Ecosystem service multifunctionality and trade-offs in English Green Belt peri-urban planning - Kirby, Matthew G.; Zawadzka, Joanna Ewa; Scott, Alister J. (Elsevier, 2024)
Green Belt policies govern peri-urban landscapes globally by restricting built development. Yet, they often have little consideration for the land within them. This is especially the case in England where ecosystem services are poorly accounted for in Green Belt policy, whilst also being viewed as a development obstacle, with few environmental and social benefits; a situation mirrored in peri-urban landscapes globally. Moreover, there is a significant research gap into Green Belts through the socio-ecological lenses of ecosystem services and multifunctionality, which allows populist discourses to go unchallenged. Using modelling and participatory mapping data this paper addresses this gap by quantifying the ecosystem service supply, trade-offs and multifunctionality of the North-East Green Belt, and the wider planning and policy implications. The results show that contrary to claims, Green Belts in England can and do provide multiple benefits to people when studied through these lenses. However, levels of individual ecosystem services and overall multifunctionality differ spatially within Green Belts resulting in opportunity areas as well as potential losses of ecosystem services from development. Areas of deciduous and coniferous woodland as well as key “green wedges” close to urban populations were found to be multifunctionality “hots-spots”, whereas arable and improved grassland provide notable “cold-spots”. Trade-offs were mostly from provisioning services. We argue that Green Belt policies explicitly and holistically accounting for ecosystem services could catalyse a multifunctional opportunity space for climate, nature and people in peri-urban landscapes. Additionally, our study demonstrates the conceptual merits of ecosystem service multifunctionality for planning.
Keywords: Landscape Planning; Multifunctionality; Planning Policy; Ecosystem Services; InVEST; Peri-Urban